2014
DOI: 10.4314/wsa.v40i1.12
|View full text |Cite
|
Sign up to set email alerts
|

Satellite-based annual evaporation estimates of invasive alien plant species and native vegetation in South Africa

Abstract: In this study we assessed the impact that invasive alien plant species (IAPs), and the clearing thereof by the Working for Water (WFW) programme, have on total evaporation (ET) and the availability of water resources in two highly-invaded provinces of South Africa. The Surface Energy Balance Algorithm for Land (SEBAL) model, using MODIS satellite imagery, was used to estimate the annual total ET at 250 m pixel resolution. ET was estimated for 3 climatically different years for the Western Cape and KwaZulu-Nata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…However, a number of species with relatively low biomass (e.g. Chromolaena, Lantana) have been found to have relatively high evapotranspiration rates, comparable to large trees (Meininger and Jarmain, 2014). For this assessment, speciesspecific reduction factors were adopted, building on the initial relationships developed by Scott and Smith (1997) and applied to invading species by Cullis et al (2007) and Mallory et al (2011).…”
Section: Estimating Species-specific Reduction Factorsmentioning
confidence: 99%
“…However, a number of species with relatively low biomass (e.g. Chromolaena, Lantana) have been found to have relatively high evapotranspiration rates, comparable to large trees (Meininger and Jarmain, 2014). For this assessment, speciesspecific reduction factors were adopted, building on the initial relationships developed by Scott and Smith (1997) and applied to invading species by Cullis et al (2007) and Mallory et al (2011).…”
Section: Estimating Species-specific Reduction Factorsmentioning
confidence: 99%
“…has transformed the grasslands [13,15], affecting rangeland production. Coordinated efforts of clearing IAPs [40] that have higher water use relative to indigenous vegetation [41] are underway to increase the proportion of water available to maintain other ecosystem services provided by rangelands [42,43]. Figure 2 provides an overview of the processing steps described in this section to perform trend analysis and characterize carbon fluxes (NEE) and water use in the catchments.…”
Section: Methodsmentioning
confidence: 99%
“…impact of clouds, resolution of images in time and space, requirements for verification on the ground), but also the potential to estimate the water resource impacts of a wide range of invasive alien plants in a consistent manner over a large area, and compare them with other land cover classes (Gibson et al 2013;Meijninger and Jarmain 2014;van Niekerk et al 2018). The only study of this type thus far found that the annual evaporation from areas with invading species was greater than from adjacent areas of natural vegetation across both the Western Cape and KwaZulu-Natal (Meijninger and Jarmain 2014). This is consistent with the generally greater water-use observed in the species and stand level studies described above and a promising development.…”
Section: Extrapolating To Larger Spatial and Longer Temporal Scalesmentioning
confidence: 99%